THE UTILIZATION OF HEALTH SERVICE BY THE SCAVENGERS IN TAMANGAPA LANDFILL ANTANG - Nur Aisyah Zalmar; Sitti Raodhah; Syarfaini Syarfaini (Homes Journal = Hospital Management Studies Journal, 2020)
Background: Habits and culture will influence the way of thinking, how to behave, how to behave which is oriented towards science in dealing with health problems in order to be healthy and appropriate in utilizing health services.Objective: To know the description of the use of health services in the working area of the Tamangapa Community Health Center by scavenger at the Tamangapa Antang landfill in 2016.Method: This study uses aapproach descriptive. With a population of 120 people and a sample of 120 respondents obtained by total sampling. Result: The results showed that the social culture related to the utilization of health services in the working area of PKM Tamangapa showed that the modern category was 89.2% while that related to the traditional category was 10.8%. Social Economy shows 100% cheap opinion. Social psychology 92.5% good results. The characteristics of officers showed good results 63.3% and 36.7% sufficient. The highest utilization of health services was utilizing health services, namely 93.3% and not utilizing health services was 6.7%.Conclusion: It is hoped that with the cooperation of all parties, the community will participate in supporting the use of health facilities, and the next researchers to carry out more in-depth research.